2019
DOI: 10.1111/jpm.12525
|View full text |Cite
|
Sign up to set email alerts
|

Newly qualified nurses' perceptions of working at mental health facilities: A qualitative study

Abstract: Accessible summary What is already known about the topic? Newly qualified nurses often feel overwhelmed by the challenges of the work environment and struggle to transition into healthcare work environments. Nurses require opportunities during the transition period to develop both competence and confidence in their ability to practise independently. What the paper adds to existing knowledge? Newly qualified mental health nurses experience fear during their adaptation period, especially when they perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…It has been widely recognised that working as an NQN can be stressful and overwhelming. NQNs are exposed to high levels of responsibility, heavy workloads and both time and staff shortages (Edwards et al, 2015;Mabala et al, 2019). The qualified status appeared to lead to the NQNs feeling they were imposters, acting the role of nurse.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely recognised that working as an NQN can be stressful and overwhelming. NQNs are exposed to high levels of responsibility, heavy workloads and both time and staff shortages (Edwards et al, 2015;Mabala et al, 2019). The qualified status appeared to lead to the NQNs feeling they were imposters, acting the role of nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in this review voiced feeling fear and apprehensiveness when providing interventions for people hearing voices. In a recent studying exploring the experiences of newly qualified nurses beginning their career in mental health units in South Africa, participants also described feeling fearful when faced with the realities of a psychiatric unit (Mabala et al, 2019). It has been suggested by Happell et al (2019) that overcoming fear and anxiety is undeniably necessary when it comes to the provision of high-quality care for people experiencing mental health issues.…”
Section: Education Skills and Trainingmentioning
confidence: 99%
“…Likewise, Schwartz et al (2011) found that collaborating with team members could promote safety in mental health settings. Similarly, a study (Mabala et al, 2019) on the experiences of new nurses in South Africa indicated the importance of positive interaction within the team and the value of learning from colleagues. The team support will also assist the nurses to overcome anxiety related to the new mental health work environment (Mabala et al, 2019).…”
Section: Team Dynamics and Collegialitymentioning
confidence: 99%